The Effect of Inhaled Ipratropium Bromide as a Premedication For Bronchoscopy on Dyspnea, Cough, and Tracheobronchial Secretion - Safina Mutmainnah; Yusup Subagio Sutanto; Jatu Aphridasari; A. Farih Raharjo (Jurnal Respirologi Indonesia, 2023)
Background: Bronchoscopy is a minimally invasive procedure used for diagnostic examination and intervention of the airways. Patient comfort and cooperation during bronchoscopy are very important because they affect the success and outcome. The sympathetic anticholinergic effect of ipratropium bromide can improve procedure tolerance and airway visualization. This study was conducted to analyze the effect of inhaled ipratropium bromide as a bronchoscopy premedication for the assessment of dyspnea, cough, and tracheobronchial secretion.Methods: This was a clinical study with a quasi-experimental pretest-posttest control group design in pulmonary patients who underwent bronchoscopy at Dr. Moewardi General Hospital Surakarta in October 2021 using consecutive sampling. The subjects of the study were divided into an intervention group with inhaled ipratropium bromide and a control group without inhaled ipratropium bromide. The Borg scale of dyspnea and the visual analog scale (VAS) score of cough were assessed before and after bronchoscopy in both groups. The grading of tracheobronchial secretion was assessed during bronchoscopy.Results: Thirty-six pulmonary patients who underwent bronchoscopy were included in this study. The intervention group showed a lower Borg scale (0.28±0.57) and VAS score (3.22±8.54), lower tracheobronchial secretion grading, and there was a significant difference compared to the control (P≤0.05).Conclusion: There was a significant difference in the Borg scale of dyspnea, VAS score of cough, and the grading of tracheobronchial secretion in patients undergoing bronchoscopy as an effect of ipratropium bromide inhalation.